2023
DOI: 10.3390/biology12081063
|View full text |Cite
|
Sign up to set email alerts
|

3D Culture and Interferon-γ Priming Modulates Characteristics of Mesenchymal Stromal/Stem Cells by Modifying the Expression of Both Intracellular and Exosomal microRNAs

Matteo Bulati,
Alessia Gallo,
Giovanni Zito
et al.

Abstract: Mesenchymal stromal/stem cells (MSCs) have emerged as a therapeutic tool in regenerative medicine. Recent studies have shown that exosome (EXO)-derived microRNAs (miRNAs) play a crucial role in mediating MSC functions. Additionally, intracellular miRNAs have been found to regulate MSC therapeutic capacities. However, the molecular mechanisms underlying miRNA-mediated MSC effects are not fully understood. We used 3D culture and IFN-γ to prime/enhance the MSC therapeutic effects in terms of functional miRNAs. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…WJ-MSCs possess various differentiation, self-renewal, and paracrine regulatory functions [38,39]. Paracrine signaling and therapeutic efficacy may be affected because enhanced exosome release has also been reported in WJ-MSC-derived exosomes carrying bioactive molecules that influence various biological processes, including immunomodulation, tissue regeneration, and angiogenesis [11,40]. This study elucidated the effects of bFGF treatment on the production and characteristics of EVs derived from WJ-MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…WJ-MSCs possess various differentiation, self-renewal, and paracrine regulatory functions [38,39]. Paracrine signaling and therapeutic efficacy may be affected because enhanced exosome release has also been reported in WJ-MSC-derived exosomes carrying bioactive molecules that influence various biological processes, including immunomodulation, tissue regeneration, and angiogenesis [11,40]. This study elucidated the effects of bFGF treatment on the production and characteristics of EVs derived from WJ-MSCs.…”
Section: Discussionmentioning
confidence: 84%
“…Bulati et al were able to differentially cluster between IFN-g primed and 3D spheroid cultured MSCs by looking at their miRNA EVs (179). Many studies have shown that MSCs have increased immunomodulatory potential after 3D spheroid culture (159)(160)(161).…”
Section: Msc Priming For Enhanced Immunomodulatory Potentialmentioning
confidence: 99%
“…Most preclinical studies involving MSC-EV therapy are based on vesicles produced by MSCs [ 3 , 64 , 65 ]. Moreover, to potentiate the functional activity of MSC-EVs, the strategy of priming/preconditioning their cells of origin was explored by using chemicals, cytokines, and growth factors, as well as specific culture conditions [ 3 , 64 , 66 , 67 , 68 , 69 ]. For instance, human MSC-EVs produced after stimulation with dimethyloxaloylglycine further stimulated angiogenesis through the Akt/mTOR pathway to enhance bone healing [ 70 ].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…Furthermore, several studies explored the effects of inflammatory priming on MSC-EVs, revealing distinct EV functions compared to other priming conditions. For instance, it was recently demonstrated that EVs derived from IFN-γ-primed MSCs have improved immunomodulatory properties compared to the 3D culture priming of MSC-EVs, which instead showed enhanced angiogenic properties [ 66 ]. In this scenario, the yield, size, and surface marker composition of MSC-derived EVs exhibited substantial variations with various priming treatments, and it is intriguing to understand how the EV content and their beneficial properties can be modulated.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%